Comment on "Contemporary art: cultivating Feng Zikai’s teachings" - Hanying Chen (Trans/Form/Ação)
Commented article: XIE, J. Y.; CHEN, X. M. Contemporary Art: Cultivating Feng Zikai's Teachings. Trans/Form/Ação: revista de filosofia da Unesp, v. 47, n. 4, “Eastern thought”, e02400120, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15089.